1980
DOI: 10.1029/jb085ib11p06572
|View full text |Cite
|
Sign up to set email alerts
|

Lunar near‐surface shear wave velocities at the Apollo Landing Sites as inferred from spectral amplitude ratios

Abstract: We reexamined the horizontal‐to‐vertical amplitude ratios of the long‐period seismograms to determine the shear wave velocity distributions at the Apollo 12, 14, 15, and 16 lunar landing sites. Average spectral ratios, computed from a number of impact signals, were compared with spectral ratios calculated for the fundamental mode Rayleigh waves in media consisting of homogeneous, isotropic, horizontal layers. The shear velocities of the best fitting models at the different sites resemble each other and differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 9 publications
8
30
0
Order By: Relevance
“…Cooper et al [141], using travel time inversion of refracted P -waves, found that the compresionnal wave velocity beneath the Apollo 17 site was around 100 m/s from 0 to 4 m depth and then 327 m/s from 4 to 32 m depth. Our shear wave profile thus complements and is consistent with previous observations [141,145]. Thus, by comparing these profiles, we can conclude that the v P /v S ratio of the Lunar regolith is ∼2.…”
Section: Lunar Subsurface Investigated From Correlation Of Seismic Noisesupporting
confidence: 79%
“…Cooper et al [141], using travel time inversion of refracted P -waves, found that the compresionnal wave velocity beneath the Apollo 17 site was around 100 m/s from 0 to 4 m depth and then 327 m/s from 4 to 32 m depth. Our shear wave profile thus complements and is consistent with previous observations [141,145]. Thus, by comparing these profiles, we can conclude that the v P /v S ratio of the Lunar regolith is ∼2.…”
Section: Lunar Subsurface Investigated From Correlation Of Seismic Noisesupporting
confidence: 79%
“…Reevaluation of published lunar geophysical data (Horvath et al, 1980;Toksoz et al, 1972) by Lognonne et al (2003) shows longitudinal seismic velocity as low as $1 km s À1 above $1 km depth below the lunar surface and an increase of 3-4 km s À1 to a depth of $5 km, which is in agreement with and constrains the validity of a porous scaling law for lunar impacts applied for a 1 km thick upper layer (Ivanov, 2006). Present results from the GRAIL mission suggest significant density variations for the …”
Section: The Earth-moon Systemsupporting
confidence: 56%
“…Our shear wave profile thus complements their P-wave profile, giving the v P /v S ratio of the lunar regolith at this site of ~2. The present result is also consistent with the S-wave velocity profiles derived from the H/V spectral amplitude ratios at other Apollo sites (Horvath et al, 1980), where they generally increase from 40 m/s at the surface to about 400 m/s at depths between 95 m and 160 m. …”
Section: Imagingsupporting
confidence: 92%